ANALISIS PERATAAN LABA DAN PENGARUHNYA TERHADAP REAKSI PASAR DAN RISIKO INVESTASIPADA PERUSAHAAN PUBLIK DI INDONESIA - Agriyanto, Ratno (Jurnal Ilmiah Infokam, 2006)
Profit is an important factor to estimate the performance of the company as one of the basis for the investor to estimate the future profit. This matter has made the investor  pay much attention to the profit of a company without noticing the proccess of the forming of profit information. This condition support the manager to do “profit management”. One of “ profit management” measurement is doing a income smoothing. The aims of the research are: 1) To analyze the market reaction between profit smoother company and non profit smoother company. 2) To analyze the difference of invesment risk between profit share company and non  profit share company. This research was conducted in Jakarta Stock Exchange (JSX) and involving 333 companies which were signed up in Jakarta stock Exchange (JSX). Through purposive  sampling method, 62 companies were taken  as samples. According to index exckel measurement, the samples are divided into 48 companies as the profit smoother and 14 companies as the non profit smoother. The data of the research is submitted by documentation. The data is analyzed by multiple regression analysis and independent t- sample test, after fulfilling  several test requirements and classic assumption. The result of the study shows that, market reaction that is observed for 3 days after the profit announcement did not show the difference of market reaction and investment risk between profit smoother company and non profit smoother company  with 5%  of the significant rate. The result of the research give implication to the future research to analyze the same topic by including other variables which give significant influence to market reaction and invesment risk, either quantitative data or qualitative data. Also to examine the causes of the appearance of the some hypotesis research  which is either significant or unsignificant.   Keyword :Imcome Smoothing, Market Reaction, Invesment Risk